Adaptation and Psychometrics Properties of Multidimensional Teachers Resilience Scale Indonesian Version (MTRS-I) - Amanda Nurshadrina; Pratiwi Widyasari; Eva Septiana; Annisa Ainina Novara; Nabila Aysha Raina Irawan (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This study aims to adapt and examine the psychometric properties of the Multidimensional Teachers Resilience Scale Indonesia Version (MTRS-I). The study about teacher resilience in Indonesia is still limited and uses the general resilience scale. There is no measurement that is specific to teacher resilience that can be used. This study used a quantitative research approach with a cross-sectional design for adapting the Multidimensional Teachers Resilience Scale (MTRS). Participants were obtained by convenience sampling. A total of 408 teachers in Indonesia participated in this study. Data was collected through a survey method using Google Forms, distributed through social media and the nearest school whose teachers were willing to participate. Data was analyzed using confirmatory factor analysis to confirm the validity and internal consistency for reliability. The result demonstrated that MTRS-I has a good-fit model. All items have factor loading of greater than 0.6, which are well-defined factors. The reliability study showed good results, either for the total score or the score of each dimension. Therefore, MTRS-I had met adequate validity and reliability. There were 13 items which were divided into four dimensions, namely emotional resilience, motivational resilience, professional resilience, and social resilience. Thus, MTRS-I is beneficial to measure teacher resilience in Indonesia.